2018
DOI: 10.1186/s13293-018-0191-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the traumatic stress response: PTSD symptoms in women recapitulated in female rats

Abstract: BackgroundPost-traumatic stress disorder (PTSD) affects men and women differently. Not only are women twice as likely as men to develop PTSD, they experience different symptoms and comorbidities associated with PTSD. Yet the dearth of preclinical research on females leaves a notable gap in understanding the underlying neuropathology of this sex difference.MethodsUsing two standard measures of PTSD-like responses in rats, the acoustic startle response (ASR) and dexamethasone suppression test (DST), we tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 65 publications
4
61
0
Order By: Relevance
“…In addition to stressor-specific differences seen in the present study, sex differences in psychological stress-induced bladder dysfunction and brain responses have previously been reported. A recent study identified consistent sex-specific differences in the brain responses to trauma in male and female rats using two models of post-traumatic stress disorder (Pooley et al, 2018). We found a significant increase in voiding frequency in female mice following water avoidance stress (West et al, 2019), an effect that has also been reported in female rats (Smith et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…In addition to stressor-specific differences seen in the present study, sex differences in psychological stress-induced bladder dysfunction and brain responses have previously been reported. A recent study identified consistent sex-specific differences in the brain responses to trauma in male and female rats using two models of post-traumatic stress disorder (Pooley et al, 2018). We found a significant increase in voiding frequency in female mice following water avoidance stress (West et al, 2019), an effect that has also been reported in female rats (Smith et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…SPS increased the latency of pairhoused Sprague-Dawley females to approach a novel rat in the social preference/avoidance test, implying an anxious phenotype, but decreased the latency of single housed females, implying social support seeking 58 . The dexamethasone suppression test revealed an exaggerated negative feedback control of the HPA axis in SPS-exposed Sprague-Dawley males, but not in females 59 . SPS lacks ecological validity and its stressor intensity cannot be modified.…”
Section: Single Prolonged Stressmentioning
confidence: 81%
“…While initial acute cat exposure studies assessed overall behavior through tests of risk assessment, anxiety, and arousal 92 , later reports also found avoidance of traumareminder in the open field test 95 , with spatial memory retention impairments in the MWM and radial-arm water maze 93,96 . Like SPS, exposure enhanced dexamethasone suppression of CORT in Sprague-Dawley males, but not in females 59 . In addition, acute ferret exposure in Sprague-Dawley rats produced sensorimotor gating abnormalities in prepulse inhibition 94 .…”
Section: Predator Stressmentioning
confidence: 93%
“…Among candidate genes that are related to stress disorders, Dopamine Transporter (DAT) disruptions have captured some attention, particularly with regards to PTSD [ 9 , 10 , 11 , 12 ]. Importantly, within PTSD affected individuals, there is higher incidence and prevalence of stress-related disorders in women [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], who show more severe symptoms and poorer treatment outcomes than men [ 21 ].…”
Section: Introductionmentioning
confidence: 99%